Association Between Maternal Anemia and the Anthropometric Measurements of Full-Term Newborns - Kiran , Wajeeha; Babar , Habibullah; Noor , Mahal; Hussain , Muhammad; Ibrahim , Muhammad; Komal (Indus Journal of Bioscience Research, 2025)
Background: Anemia during pregnancy continues to be a serious public health concern, especially in poorer nations where it strongly increases mother and newborn morbidity and mortality. This study highlights the effect of maternal hemoglobin levels on fetal growth by examining the connection between maternal anemia and neonatal anthropometric measurements. Methods: From January 2024 to January 2025, a cross-sectional descriptive study was carried out at the Gynaecology and Obstetrics Department of a Quetta tertiary care hospital. A straightforward sample strategy was used to choose 300 full-term pregnant women between the ages of 18 and 40. Maternal anemia was classified as mild (10.9–9.0 g/dl), moderate (8.9–7.0 g/dl), and severe (